PENGARUH BIAYA OPERASIONAL (BOPO), BAGI HASIL DANA PIHAK KETIGA (DPK), CASH RATIO TERHADAP MARGIN MURABAHAH PADA BANK UMUM SYARIAH - Lady Vini Maharani Lubis; Zufrizal Harahap; Zenni Riana; Sri Rahayu; Syamsul Effendi; Eli Agustami (JRAM (Jurnal Riset Akuntansi Multiparadigma), 2021)
The purpose of this study is to analyze whether Operational Costs (BOPO) affect Murabahah Margin in Sharia Commercial Banks, know whether Third Party Fund Revenue Sharing (DPK) affects Murabahah Margin in Sharia Commercial Banks, know if Cash Ratio affects Murabahah Margin in Sharia Commercial Banks. And aims to find out if Operational Costs (BOPO), Third Party Fund Revenue Sharing (DPK), and Cash Ratio jointly affect Murabahah Margin in Sharia Commercial Banks from 2016 to 2019. The data analysis methods used to test hypotheses in this study are descriptive analysis tests, classic assumption tests, multiple linear regression analysis tests, and hypothesis tests. The results of this study showed that variable Operational Costs (BOPO), Third Party Fund Revenue Sharing (DPK), and Cash Ratio simultaneously or jointly have a significant influence on Murabahah Margin. While partially having different influences, Operating Costs (BOPO) have a positive and significant effect on Murabahah Margin, Third Party Fund Revenue Share (DPK) has no significant effect on Murabahah Margin, and Cash Ratio has no significant effect on Murabahah margin.